Different susceptibility to pramipexole-induced impulsivity in a rat model of parkinson’s disease - Jiménez-Urbieta, Haritz; Merino-Galan, Leire; Rodriguez-Chinchilla, Tatiana; Belloso-Iguerategui, Arantzatzu; Delgado-Alvarado, Manuel; Navalpotro-Gómez, Irene; Quiroga-Varela, Ana; Gago-Calderón, Belén; Rodríguez-Oroz, María Cruz (My University, 2019)
Impulse Control Disorders (ICD) in patients with Parkinson’s disease are abnormal behaviors caused by long-term use of dopamine agonists, which pathophysiology is poorly understood. Using parkinsonian rats (adeno-associated viral vectors-mediated overexpression of A53T human α-synuclein in the substantia nigra compacta), we evaluated the impulsive behaviour under acute (0.25 and 3 mg/kg) and chronic (0.25 mg/kg for 4 weeks) administration of pramipexole (PPX) with the Variable Delay-to-Signal (VDS) task (motor and choice impulsivities). Changes in striatal D1 and D2 receptors expression were also analysed. Before treatment, the striatal dopaminergic depletion caused a significant increase of both impulsivity domains with respect to basal condition. In lesioned rats, acutely given PPX 0.25 mg/kg dose increased choice impulsivity only with regard to basal values. Meanwhile, 3 mg/kg PPX increased choice impulsivity compared to their own values at different conditions: basal, before treatment and after acute 0.25 mg/kg PPX administration. After chronic administration, two populations of lesioned animals were distinguished, one showing the same behaviour as control animals and other displaying an increased motor/response (first week of treatment) and cognitive/choice impulsivities (third week of treatment) compared to control animals. This impulsive behaviour disappeared when animals were tested in OFF state. Lower D2 expression in both Caudate-Putamen and Nucleus Accubens and lower D1 levels in Nucleus Accumbens in lesioned rats than in control animals were observed. Therefore, our results indicate that the pro-impulsive effect of PPX in this animal model of PD depends on the dose and administration paradigm employed and the individual predisposition, and it is associated to striatal dopamine receptors expression changes, especially in Nucleus Accumbens. Thus, this model could constitute a valid tool to investigate the pathophysiology of ICD.
Keywords: Parkinson, Enfermedad de; Parkinson's disease; Impulsivity; Animal model